1981
DOI: 10.1007/bf00405609
|View full text |Cite
|
Sign up to set email alerts
|

Reaction time changes among steel workers exposed to solvent vapors

Abstract: A longitudinal study was performed to investigate the behavioral changes associated with occupational exposure to organic solvents. An initial simple reaction time (SRT) test was performed on a group of steel workers who were exposed to vapor concentrations of solvents clearly exceeding threshold limit values (TLVs). A second SRT measurement was made six months following the completion of major improvements in the hygiene quality of the work environment which resulted in a reduction of exposure levels to 20% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The first case reports describing a relationship between long-term occupational exposure to organic solvents and the develoment of demential and neurasthenic symptoms were published as early as the latter half of the 19th century [Delpech, 1863;Koster, 1899a,b;Laudenheimer, 18991. Since that time several cases have been published [Knabenhans, 1941;BorbCly, 1946;Mikkelsen et al, 19781, and new ones continue to be reported [Axelson, 1976;Arlien-S$borg et al, 19791. This relationship is supported by a number of epidemiological studies. In crosssectional studies of workers, standardized psychological tests have demonstrated that in exposed workers, intellectual functions were impaired compared to nonexposed workers [Grandjean et al, 1955;Gamberale and Svensson, 1974;Gamberale et al, 1976;Hiinninen et al, 1976;Lindstrom et al, 1976;Hane et al, 1977;Knave et al, 1978;Elofsson et al, 1980;Anshelm-Olson et al, 1979;Gregersen et al, 19841.…”
Section: Introductionmentioning
confidence: 99%
“…The first case reports describing a relationship between long-term occupational exposure to organic solvents and the develoment of demential and neurasthenic symptoms were published as early as the latter half of the 19th century [Delpech, 1863;Koster, 1899a,b;Laudenheimer, 18991. Since that time several cases have been published [Knabenhans, 1941;BorbCly, 1946;Mikkelsen et al, 19781, and new ones continue to be reported [Axelson, 1976;Arlien-S$borg et al, 19791. This relationship is supported by a number of epidemiological studies. In crosssectional studies of workers, standardized psychological tests have demonstrated that in exposed workers, intellectual functions were impaired compared to nonexposed workers [Grandjean et al, 1955;Gamberale and Svensson, 1974;Gamberale et al, 1976;Hiinninen et al, 1976;Lindstrom et al, 1976;Hane et al, 1977;Knave et al, 1978;Elofsson et al, 1980;Anshelm-Olson et al, 1979;Gregersen et al, 19841.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group performed such studies with workers in the plastic boat industry who were exposed to styrene (25), workers in the steel industry exposed mainly to methyl ethyl ketone (MEK) (26), and workers in the paint manufacturing industry exposed to solvent mixtures (27).…”
Section: Brief History Of Solvent Researchmentioning
confidence: 99%